O Problema da Integração de Programas Governamentais de Desenvolvimento Regional: O Caso do Promeso - João Mendes Rocha Neto (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2014)
The public policies have been studied from different theoretical and technical aspects. However, there is still a gap that addresses several issues related to intersectoral and integration of actions among governmental agencies. These issues when studied approach little to the perspective of the impacts of the architectural structure of Brazilian institutions on public policies. Thus, the research sought to identify where that disjoined character manifests, from the literature on intersectionality, and then explain, through documentary research, this gap between the official coordinated action and practical implementation. The developmentof the research required a theoretical review that has gone from political science to regional development, through discussion of mainstreaming and intersectionality in public policy. Also the research used databases of the Secretariat of Federal Budget (SOF / MOF) and those of Integrated FinancialManagement System (Siafi/MF)as well as the official documents of the Ministry of National Integration. The last one are the documents of the Sustainable Development Program of Differentiated Mesoregions (Promeso) and also subject of aspecific study. Additionally the databases of the Superior Electoral Court (TSE) were consulted. The study came to the conclusion that public policy characterized by intersectionality, have clear marks of competition and little coordination among agencies of the federal government as they follow various logics, determined by the leaders of these agencies. The purpose of the article is to contribute to the construction of a methodology that allows to understand some of these intersectoral performance limits starting from dimensions hitherto little treated in the studies.